A Single-Case, Mixed Methods Study Exploring the Role of Music Listening in Vibroacoustic Treatment - Campbell, Elsa; Burger, Birgitta; Ala-Ruona, Esa (Voices: A World Forum for Music Therapy, 2019)
Chronic pain is a widespread issue accompanied commonly by depression and anxiety. Chronic pain has been shown to alter brain processing within the emotional and reward circuits, pointing towards a possible link between pain and comorbid mood disorders. Pain relief may be achieved by alleviating depressive and anxious symptoms. Relaxation is important for pain relief and eliciting relaxation through music listening is shown to relieve pain, depression, anxiety, and discomfort among others. In addition to auditory stimuli, Vibroacoustic treatment – the tactile application of low frequency sinusoidal sound vibration, plus music listening and therapeutic interaction – has been shown to be beneficial for relieving these symptoms. Although the combination of music listening and low frequencies has been previously explored, the role of the music listening within the vibroacoustic treatment context is unknown. A single-case, mixed method crossover study was conducted with a client suffering from chronic pain and comorbid mood disorders, four sessions with music listening, and four sessions without. Quantitative outcomes showed the client was more relaxed, less anxious, and had less pain after the music sessions. Qualitative findings showed that the client at first could not relax without the music listening because of her severe anxiety, but learned to use music as a distractor from her thoughts to relax, but also that silence was equally important for her; these hinged on her making the choice based on her needs, which had previously been difficult for her.